IMPACT OF ECOLOGICAL ENGINEERING ON THE TYPE AND POPULATION OF PESTS, NATURAL ENEMIES, AND YIELDS OF THE RICE - Usyati, N; Kurniawati, Nia; Rumasa, Oco (Universitas Lampung, 2020)
Impact of ecological engineering on the type and population of pests, natural enemies, and yields of the rice. This studywas performed to investigate the impact of the ecological engineering in the rice field on the crop damage caused by yellowstem borer, including it’s type and population as well as its natural enemies and the yields of the rice. The study wasconducted in farmer’s fields in Subang District in the dry and the wet seasons. The research was arranged using RandomizedComplete Block Design (RCBD) with 9 treatments and 3 replications. The observation was conducted on the crop damagecaused by yellow stem borer, the type and the population of pests insect, its predator, and parasitoid as well as yields of therice. The planting of flowering plants and crops showed inconsistent effect on the population of brown planthoppers, whitebacked planthoppers, and rice black bug. Moreover, it also not significantly impact the yellow stem borer. The planting offlowering plants and crops did not affect the rice yields. The parasitization level of the parasitoid was in ranged of 47.32–50.47% (dry season) and 36.37–53.92% (wet season). The neutral insect population was dominant at the beginning of planting(11–1743), meanwhile at the maximum tillering until the harvest was dominated by predators (9.33–131.33). The parasitoidswere relatively contrasted on each stage of the rice plant.